Clinical Characteristics, Histopathology, and Tissue Immunolocalization of Chikungunya Virus Antigen in Fatal Cases. (2nd July 2020) - Sharp, Tyler M; Keating, M Kelly; Shieh, Wun-Ju; Bhatnagar, Julu; Bollweg, Brigid C; Levine, Rebecca; Blau, Dianna M; Torres, Jose V; Rivera, Aidsa; Perez-Padilla, Janice; Munoz-Jordan, Jorge; Sanabria, Dario; et al.
Abstract: Background: Death in patients with chikungunya is rare and has been associated with encephalitis, hemorrhage, and septic shock. We describe clinical, histologic, and immunohistochemical findings in individuals who died following chikungunya virus (CHIKV) infection. Methods: We identified individuals who died in Puerto Rico during 2014 following an acute illness and had CHIKV RNA detected by reverse transcriptase–polymerase chain reaction in a pre- or postmortem blood or tissue specimen. We performed histopathology and immunohistochemistry (IHC) for CHIKV antigen on tissue specimens and collected medical data via record review and family interviews. Results: Thirty CHIKV-infected fatal cases were identified (0.8/100 000 population). The median age was 61 years (range: 6 days–86 years), and 19 (63%) were male. Death occurred a median of 4 days (range: 1–29) after illness onset. Nearly all (93%) had at least 1 comorbidity, most frequently hypertension, diabetes, or obesity. Nine had severe comorbidities (eg, chronic heart or kidney disease, sickle cell anemia) or coinfection (eg, leptospirosis). Among 24 fatal cases with tissue specimens, 11 (46%) were positive by IHC. CHIKV antigen was most frequently detected in mesenchymal tissues and mononuclear cells including tissue macrophages, blood mononuclear cells, splenic follicular dendritic cells, and Kupffer cells. Common histopathologic findings were intra-alveolar hemorrhage and edema in the lung, chronic or acute tenosynovitis, and increased immunoblasts in the spleen. CHIKV infection likely caused fatal septic shock in 2 patients. Conclusions: Evaluation of tissue specimens provided insights into the pathogenesis of CHIKV, which may rarely result in septic shock and other severe manifestations. Abstract : After collection of tissue specimens from fatal cases, we observed chikungunya virus infection in a wide variety of human tissues, particularly mesenchymal tissues and mononuclear cells. In rare cases, chikungunya virus was likely an etiologic agent of septic shock.